OPTIMALISASI KESEHATAN IBU NIFAS DENGAN SENAM NIFAS - Ilmiatus Qoyimah (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2023)
The puerperium begins when the placenta is born and ends when the uterine organs return to pre-pregnancy. Postpartum mothers will experience many physical and psychological changes. Postpartum gymnastics is one way to help the mother recover soon, it aims to expedite the process of uterine involution, is beneficial in terms of beauty, restores health, and improves muscle tension after pregnancy. Internal and external factors influence the implementation of postpartum exercise. The formulation of the problem is in the form of limited knowledge and skills about postpartum exercise in the working area of the Talagasari Health Center, Karawang Regency, due to the absence of socialization and guidance regarding postpartum exercise. The purpose of the service is to increase knowledge and skills about postpartum exercise for postpartum mothers using modules and video media so that it helps in carrying out postpartum exercises independently and as an additional program for pregnant women's classes. The service method in the socialization and guidance of postpartum gymnastics uses question-and-answer lectures, discussions, simulations, and practice of postpartum gymnastics, accompanied by pre-tests and post-tests. The activity was carried out for three months in the homes of 185 respondents. The results of this socialization activity and postpartum exercise guidance have implications in the form of increasing the knowledge of postpartum mothers up to 9.28. Activities have provided benefits in the form of increased knowledge and skills about postpartum exercise for all respondents. The conclusion is that postpartum exercise socialization and guidance activities have implications in the form of increasing knowledge and ability to carry out postpartum exercise movements independently using postpartum exercise modules and videos. Furthermore, the health center can continue the postpartum exercise activities in the postnatal care material in the class program for pregnant women.